1997
DOI: 10.1046/j.1365-2672.1997.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial influence on the production of paralytic shellfish toxins by dinoflagellated algae

Abstract: This study investigated the role of intracellular and extracellular bacteria in the production ofparalytic shellfish toxins by dinoflagellated algal cells. Three strains of the toxic dinoflagellatespecies, Alexandrium tamarense, were purified by external bacteria using penicillin G (Pen.G) at levels of 500 and 1000 p.p.m. Levels of toxicity of the resulting purified dinoflagellatecultures were similar to those of the original strains contaminated with external bacteria,indicating that the external bacteria had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…It is commonly accepted that microalgae are associated with bacteria which can be either free in the surrounding phycosphere, attached externally on the surface membrane, or within cells in small inclusions (reference 55 and references therein). This was also demonstrated for some dinoflagellates by transmission electron microscopy (35), by fluorescent in situ hybridization, or through bacterial isolation and culturing (8,16,20). As a result, native bacteria are probably always included in cultures when cultures are initiated from resting cysts or vegetative cells.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It is commonly accepted that microalgae are associated with bacteria which can be either free in the surrounding phycosphere, attached externally on the surface membrane, or within cells in small inclusions (reference 55 and references therein). This was also demonstrated for some dinoflagellates by transmission electron microscopy (35), by fluorescent in situ hybridization, or through bacterial isolation and culturing (8,16,20). As a result, native bacteria are probably always included in cultures when cultures are initiated from resting cysts or vegetative cells.…”
Section: Discussionmentioning
confidence: 75%
“…in Cork Harbor in June 2004. The use of toxins to establish taxonomic relationships does not usually appear to be reliable because too many external parameters, such as bacterial activity, salinity, or nutrient concentrations, may influence both the toxin synthesis and the toxin profile (16,29,38). Within the Irish context, however, the presence of toxin could be a discriminative character, allowing strains isolated from the south coast to be distinguished from those isolated from the west coast, a distinction morphology does not allow.…”
Section: Discussionmentioning
confidence: 99%
“…Although roseobacters are widespread throughout the marine ecosystem, their abundance is significantly correlated with DMSP-producing algae, especially prymnesiophytes and dinoflagellates, such as Prorocentrum, Alexandrium, and Pfiesteria species (1,14,27).…”
mentioning
confidence: 99%
“…Nevertheless, several authors have reported on the production of PST by 'axenic' dinoflagellate cultures with levels of toxicity similar to those observed for non-axenic strains (Dantzer & Levin 1997, John & Flynn 1999 but the absence of bacteria (free, attached or endocellular) was not clearly demonstrated. Tosteson et al (1989) and suggested that bacteria could modify algal toxicity via attachment.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 89%
“…The demonstration of PST production after inoculation of a bacterial strain into non-toxic dinoflagellate cultures (Silva & Sousa 1981, Silva 1990, the modification of the toxin profile after a bactericidal treatment of a toxic dinoflagellate culture (Hold et al 2001) and the autonomous bacterial production of phycotoxins (Gallacher et al 1997 has, in some cases, cast doubt that these toxins are indeed produced by the algae alone (see reviews by Rausch de Traubenberg & Lassus 1991. Nevertheless, several authors have reported on the production of PST by 'axenic' dinoflagellate cultures with levels of toxicity similar to those observed for non-axenic strains (Dantzer & Levin 1997, John & Flynn 1999 but the absence of bacteria (free, attached or endocellular) was not clearly demonstrated. Tosteson et al (1989) and suggested that bacteria could modify algal toxicity via attachment.…”
Section: Introductionmentioning
confidence: 89%